Enhanced antitumor immunity via endocrine therapy prevents mammary tumor relapse and increases immune checkpoint blockade sensitivity - Sequeira, Gonzalo Ricardo (2021)
The role of active antitumor immunity in hormone receptor–positive (HR+) breast cancer has been historically underlooked. The aim of this study was to determine the contribution of the immune system to antiprogestin-induced tumor growth inhibition using a hormone-dependent breast cancer model. BALB/c-GFP+ bone marrow (BM) cells were transplanted into immunodeficient NSG mice to generate an immunocompetent NSG/BM-GFP+ (NSG-R) mouse model. Treatment with the antiprogestin mifepristone (MFP) inhibited growth of 59–2-HI tumors with similar kinetics in both animal models. Interestingly, MFP treatment reshaped the tumor microenvironment, enhancing the production of proinflammatory cytokines and chemokines. Tumors in MFP-treated immunocompetent mice showed increased infiltration of F4/80+ macrophages, natural killer, and CD8 T cells, displaying a central memory phenotype. Mechanistically, MFP induced immunogenic cell death (ICD) in vivo and in vitro, as depicted by the expression and subcellular localization of the alarmins calreticulin and HMGB-1 and the induction of an ICD gene program. Moreover, MFP-treated tumor cells efficiently activated immature dendritic cells, evidenced by enhanced expression of MHC-II and CD86, and induced a memory T-cell response, attenuating tumor onset and growth after re-challenge. Finally, MFP treatment increased the sensitivity of HR+ 59–2-HI tumor to PD-L1 blockade, suggesting that antiprogestins may improve immunotherapy response rates. These results contribute to a better understanding of the mechanisms underlying the antitumor effect of hormonal treatment and the rational design of therapeutic combinations based on endocrine and immunomodulatory agents in HR+ breast cancer.